Influence Analysis of DPS, EPS, and PBV toward Stock Price and Return - Sebastianus Laurens (Bina Nusantara University, 2018)
The research revealed whether there was a significant influence of DPS, EPS, and PBV towards stock price and return. This research used a quantitative method to determine the influence of the independent variable towards the dependent variable. The quantitative analysis was conducted with statistic technic calledmultiple linear regression with data taken from Indonesia Capital Market Directory year 2005 and 2008. The result shows similar results with the previous research that there is no influence between DPS and stock price as well as there is an influence on stock return. EPS shows that there is influence of stock price and return. For PBV, there is an influence on stock price, but there is no an influence on stock return.